Sport psychology interventions with young athletes: the perspective of the sport psychology practitioner - Henriksen, K.; Larsen, C. H.; Storm, L. K.; Ryom, K. (Journal of Clinical Sport Psychology, 2014)
Young competitive athletes are not miniature elite athletes; they are a distinct client group to whom sport psychology practitioners (SPPs) increasingly deliver services. Interventions with this client group are often undertaken by newly educated SPPs who are in need of good guiding principles. Yet, there is a lack of research informing SPPs` work with this group. In this current study, semistructured qualitative interviews were conducted with four experienced practitioners about their most successful interventions in competitive youth sport. Analysis showed three major themes: (a) young athletes should be equipped with a holistic skills package that enables them to handle a number of existential challenges; (b) young athletes are embedded in an environment (coaches, experts, teammates etc.) that should be involved in the interventions; and (c) interventions with young athletes should maintain a long-term focus. These themes are discussed in the context of current literature on sport psychology service delivery.